Impact of Out-of-pocket Costs on Varenicline Utilization and Persistence - Aaron Galaznik; Katherine Cappell; Leslie Montejano; Geoffrey Makinson; Kelly H. Zou; Gregory Lenhart (Journal of Health Economics and Outcomes Research)
**Background:** Varenicline is a smoking cessation medication.